(untitled) (Agricultural Engineering, 2019)
The size of all sensible heat balance components in livestock building varies in time, because it depends on time-varying weather factors. On the example of two buildings, sensible heat balance was shown on a daily basis. Measurements carried out in winter and spring in two livestock buildings with usable attics included measurements of air temperature and humidity inside and outside, air velocity in ventilation channels, and wind speed. Measuring devices were designed to record the results of measurements at intervals of 300s. During each such time interval, sensible heat losses by ventilation, heat losses by permeation through the barrier construction, and the amount of sensible heat produced by the animals were calculated. The results of measurements were shown in graphs. The study is important for the development of animal livestock building.